Retardation of uranium and thorium by a cementitious backfill developed for radioactive waste disposal. (July 2017) - Felipe-Sotelo, M.; Hinchliff, J.; Field, L.P.; Milodowski, A.E.; Preedy, O.; Read, D.
Abstract: The solubility of uranium and thorium has been measured under the conditions anticipated in a cementitious, geological disposal facility for low and intermediate level radioactive waste. Similar solubilities were obtained for thorium in all media, comprising NaOH, Ca(OH)2 and water equilibrated with a cement designed as repository backfill (NRVB, Nirex Reference Vault Backfill). In contrast, the solubility of U(VI) was one order of magnitude higher in NaOH than in the remaining solutions. The presence of cellulose degradation products (CDP) results in a comparable solubility increase for both elements. Extended X-ray Absorption Fine Structure (EXAFS) data suggest that the solubility-limiting phase for uranium corresponds to a becquerelite-type solid whereas thermodynamic modelling predicts a poorly crystalline, hydrated calcium uranate phase. The solubility-limiting phase for thorium was ThO2 of intermediate crystallinity. No breakthrough of either uranium or thorium was observed in diffusion experiments involving NRVB after three years. Nevertheless, backscattering electron microscopy and microfocus X-ray fluorescence confirmed that uranium had penetrated about 40 μm into the cement, implying active diffusion governed by slow dissolution-precipitation kinetics. Precise identification of the uranium solid proved difficult, displaying characteristics of both calcium uranate and becquerelite. Highlights: CDP increase the solubility of U and Th under hyper-alkaline conditions in repository. Solids with characteristics of calcium uranate and becquerelite control U solubility. CDP causes increase of the diffusion of U through a cementitious backfill (NRVB).